2012
DOI: 10.1016/j.jadohealth.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Subtype Differentially Predicts Smoking Expectancies in Adolescents

Abstract: ADHD subtype differentially predicted smoking expectancies. Adolescents with ADHD may be more vulnerable to developing pro-smoking expectancies due to subtype-related deficits in neurocognitive processing. These findings have potential implications for developing targeted smoking prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
5
8
2
Order By: Relevance
“…It was shown that adolescents with inattention were more reluctant to accept the negative consequences of smoking. This contrasts with those with clinical type of hyperactivity/impulsivity who more appreciated the positive consequences, such as 'expected benefit' (OR = 5.3), 'affect control' (OR = 2.6), and 'reduced boredom' (OR = 3.1) (Foster, Racicot, & McGrath, 2012). Of further note is that in this study inattentive female adolescents appreciated well reduced weight as a consequence of smoking.…”
Section: Adhd and Smoking Initiationcontrasting
confidence: 75%
See 1 more Smart Citation
“…It was shown that adolescents with inattention were more reluctant to accept the negative consequences of smoking. This contrasts with those with clinical type of hyperactivity/impulsivity who more appreciated the positive consequences, such as 'expected benefit' (OR = 5.3), 'affect control' (OR = 2.6), and 'reduced boredom' (OR = 3.1) (Foster, Racicot, & McGrath, 2012). Of further note is that in this study inattentive female adolescents appreciated well reduced weight as a consequence of smoking.…”
Section: Adhd and Smoking Initiationcontrasting
confidence: 75%
“…The hypothesis that typical traits of ADHD predispose for early smoking initiation and nicotine dependence (Foster, Racicot, & McGrath, 2012;Hakulinen et al, 2015;Kvaavik & Rise, 2012) and make it difficult to quit smoking may partly explain the high prevalence of tobacco use among ADHD subjects. One would therefore expect that treatment of ADHD with methylphenidate would subside or dampen these predisposing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Negative affect may predispose adolescents to perceive ND symptoms and expect smoking will help curb unpleasant emotions. Foster et al (2012) found never-smoking adolescents with clinical levels of impulsivity were more likely to believe smoking controls affect and reduces boredom. These adolescents are at increased risk of initiating smoking.…”
Section: Discussionmentioning
confidence: 92%
“…The aim of the current study was to examine whether greater exposure to airborne nicotine via SHS increases risk of initiation precursors among never-smoking adolescents. Precursors were selected intentionally on the basis of their established relations with smoking behavior and included the following: (1) smoking expectancies, which develop before smoking initiation 39 and contribute to smoking 40 ; (2) aversion to SHS exposure, which is associated with home smoking bans, 41 and in turn, a lower likelihood of smoking initiation 42 ; (3) nicotine dependence symptoms among adolescent never-smokers, 43 which predict the first cigarette puff 24 ; and (4) smoking susceptibility, which is a well-established predictor of smoking initiation 38 and is associated with sensitivity to SHS exposure. 34 This study investigated the differential effects of social exposure to smoking and pharmacological exposure to airborne nicotine on smoking precursors.…”
mentioning
confidence: 99%